Model of Character Education for Students with Autism: Its Conception and Application in Special School Education Institutions - Widiani, Desti (Proceeding International Conference on Religion, Science and Education, 2022)
This research is based on the assumption that it is necessary to internalize character education in children with autism. The increasing number of children with autism is a problem that is a shared responsibility, not just the medical department or psychologist. In terms of behavior, children with autism tend to hurt themselves, not confident and aggressive. From these problems, character education also plays a role in directing them to become independent and useful human beings according to their abilities so as not to become a burden on the contrary is a gift given by Allah swt. One of the schools that deal with the problem of children with autism is the Special School “Taruna Al-Qur’an Yogyakarta”. This research is a qualitative research that uses an educational psychology approach. The data collection techniques using interviews, observation and documentation. While the data analysis uses data collection, data reduction, data presentation, triangulation and conclusion drawing. The purpose of this research is to find out the model of character education for children with autism, then what character education values have been successfully developed, as well as what are the supporting and inhibiting factors in character education for children with autism at the Special School “Taruna Al-Qur’an Yogyakarta”.